THE EFFECT OF DISCIPLINE AND WORK MOTIVATION ON THE PERFORMANCE OF EMPLOYEES OF REGIONAL GENERAL SERVICES AGENCY (BLUD) BANGKINANG HOSPITAL - Hendra Gunawan; Zulher Zulher; Adi Setiawan (Jurnal Riset Manajemen Indonesia, 2022)
This study aims to determine the effect of discipline and work motivation simultaneously and partially on the performance of employees of the Regional Public Service Agency (BLUD) Bangkinang Hospital. The population in this study were all employees of the Regional Public Service Agency (BLUD) of Bangkinang Hospital which were known to be 124 employees. The sampling method in this study was the total sample method using the saturated census technique so that the number of samples in this study was 124 respondents. Data analysis was carried out using multiple linear regression models. Based on the test results simultaneously and partially, the variables of discipline and work motivation proved to have a significant effect on the performance of the employees of the Regional Public Service Agency (BLUD) Bangkinang Hospital. The close relationship that occurs between the variables of discipline and work motivation on employee performance is strong. The contribution of the independent variable to the dependent variable is 63.6% while the remaining 36.4% is influenced by other variables not examined in this study.